Attitudes of the elderly towards euthanasia: a cross-cultural study - Ramabele, T. (University of the Free State, 2004)
The purpose of this study was to determine attitudes of the elderly towards euthanasia. The aims of this research study were achieved by gathering data from a number of elderly respondents aged 65 and older at several old age homes in the Bloemfontein area. Six old age homes were involved in this study with a slightly greater concentration coming from Bloemfontein N=89 (44.5%), while the distribution was relatively even across the other two broader residential areas N=55 (27.5%) in Heidedal, and N=56 (28%) in Mangaung. A biographical questionnaire as well as the Euthanasia Attitude Scale was used. The influence of three variables such as, race, religious beliefs and gender, on the attitudes of the elderly people towards euthanasia was investigated. One-way ANOVA analysis was used. After statistical analysis, the variable found to have the greatest influence on the attitudes of the elderly towards euthanasia was race. Other variables, religious beliefs and gender were not found to have a significant correlation to euthanasia
Dissertation (M.A. (Clinical Psychology))--University of the Free State, 2004
Keywords: Euthanasia -- Moral and ethical aspects; Euthanasia -- Psychological aspects -- Testing; Older people -- Suicidal behavior -- Cross-cultural studies; Terminal care -- Methods -- Older people; Physician assisted suicide; Attitudes; Legalization; Race; Religious beliefs; Gender; Socio-demographic factors